Determinants of entrepreneurial success among homestay operators in Sabah - Kelvin Yong (2020)
Tre purpose of this study is to examine whether the entrepreneuria I motivatbn, entrepreneurial competencies, social media marketing and community participatbn have pa;itive relatbnsh ip towards entrepreneuria I success among homestay entrepreneurs or operators in Sabah. Secondl y, it is to predict whether age and gender do moderate the relatbnship betvveen entrepreneuria I motivatbn and entrepreneurial success. The findings of the study indicated that only entrepreneurial motivation, entrepreneurial compete ncies, and community participation have positive rela tionships towards the entrepreneurial success. As for moderating roles, only age shovvs moderating roles in the relationships between entrepreneurial motivation and entrepreneurial success. The selectbns of respondents are based on purposive sampling. This study utilized the SPSS and Smart PLS 3 software to analyze the data. Resources-based view and social exchange theory were used to develop the conceptual framework for the study. In 2018, there are 369 homestay entrepreneurs registered under Ministry of Tourism, Arts and Culture (MOTAC) in Sabah. However, only 181 useful questbnnaires were collected out of 369 homestay entrepreneurs in Sabah. The entrepreneurial success were measured based on the financial performance were it represented by business profitability, sales and return in investment. Since, the studies of entrepreneurial success were less study and explore in the in homestay context Where, past studies reveal that the homestay entrepreneurs were unable to sustain the business revenue due to lack of number of tourists or visitor arrival. This is followed by competitbn from other accommodatbn such as unregistered homestay entrepreneurs. However it was contradicted with the homestay statistic performances in 2018, where the performances of the homestay program income were very profitable. The results of this empirical data will give a clear view for Minister of Tourism, Arts and Culture (MOT AC), Institute of Rural Advancement (INFRA), and Sabah Homestay Associatbn to understand the determinants that influence the homestay entrepreneurs in sustaining their successful homestay business in Sabah. It also can contribute to the body of knowledge, theoretical, polic y makers and manageria I implicatbn.